Phenology and carbon dioxide source/sink strength of a subalpine grassland in response to an exceptionally short snow season - M Galvagno; G Wohlfahrt; E Cremonese; M Rossini; R Colombo; G Filippa; T Julitta; G Manca; C Siniscalco; U Morra di Cella; M Migliavacca (Environmental Research Letters, 2013)
Changes in snow cover depth and duration predicted by climate change scenarios are expected to strongly affect high-altitude ecosystem processes. This study investigates the effect of an exceptionally short snow season on the phenology and carbon dioxide source/sink strength of a subalpine grassland. An earlier snowmelt of more than one month caused a considerable advancement (40 days) of the beginning of the carbon uptake period (CUP) and, together with a delayed establishment of the snow season in autumn, contributed to a two-month longer CUP. The combined effect of the shorter snow season and the extended CUP led to an increase of about 100% in annual carbon net uptake. Nevertheless, the unusual environmental conditions imposed by the early snowmelt led to changes in canopy structure and functioning, with a reduction of the carbon sequestration rate during the snow-free period.